What, who and when? Incorporating a discrete choice experiment into an economic evaluation - Michela Tinelli; Mandy Ryan; Christine Bond (Health Economics Review, 2016)
Background: Economic evaluation focuses on Quality-Adjusted-Life-Years (QALYs) as the main valuation method. However, it is well known that factors beyond health related quality of life are important to patients and the public. Whilst discrete-choice-experiments (DCE) have been extensively used to value such factors, their incorporation within an economic evaluation framework is limited. This study is the first to incorporate patient preferences for factors beyond QALYs into an economic evaluation and compare results with the standard cost-per-QALY approach, using randomised-controlled-trial (RCT) participants. Methods: Costings, clinical-effectiveness (appropriateness-of-treatment), QALYs and patient satisfaction data were collected at baseline and 12-month follow-up for a new pharmacy-service within a randomised-controlled-trial. Trial participants who replied to the follow-up survey and had not subsequently withdrawn from the study were mailed a DCE questionnaire at 24-months. WTP for the standard and new service was derived from the DCE. Results from QALYs and the DCE were compared. Results: At 12 months, costs, clinical-effectiveness and QALYs did not differ between the intervention and control; however there was a significant increase in satisfaction in the intervention. The DCE valued this increased satisfaction in the intervention (positive net-benefit). The longer the time patients experienced the new service the greater the reported net-benefit. Conclusion: When incorporating a DCE into an economic evaluation a number of questions are raised: what factors should be valued, whose values (trial-groups vs. all-trial-population) and when should they be elicited (still-receiving-the-intervention or afterwards). Consideration should also be given to status quo bias.
Keywords: 330; Economic evaluation; Discrete choice experiment (DCE); Willingness to pay (WTP); Quality adjusted life year (QALY); Cost-benefit analysis (CBA); Randomised controlled trial (RCT)